Asuhan Keperawatan Medikal Bedah Pada Pasien Dengan Gagal Ginjal Kronik Stage V di Ruangan Interne Rsud Prof. H. Muhammad Yamin, SH Pariaman - Syadilla Aini Lativa; Kheniva Diah Anggita; Aulia Asman; Mike Asmaria (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
According to the World Health Organization (2025), Chronic Kidney Disease (CKD) affects approximately 9% of the world’s population and has the potential to become one of the leading causes of mortality worldwide. In Indonesia, the prevalence of CKD is reported at 0.22%, affecting approximately 638,178 people (SKI, 2023). Data from RSUD Prof. H. M. Yamin, S.H. Pariaman in 2026 recorded 335 cases of Chronic Kidney Disease with hypertension complications. This case study aimed to describe the implementation of nursing care for patients with Chronic Kidney Disease at RSUD Prof. H. M. Yamin, S.H. Pariaman in 2026. The study employed a case study approach, with data collected through observation, interviews, and documentation. The findings identified five nursing problems. Evaluation results showed that impaired gas exchange was resolved, hypervolemia remained unresolved, nutritional deficit was resolved, ineffective peripheral tissue perfusion was resolved, and disturbed sleep pattern was resolved. It can be concluded that the nursing care provided contributed to improving the quality of healthcare services and supported the recovery process of patients with Chronic Kidney Disease.